"Hood films" et films de banlieue: etude comparative des dynamiques linguistiques et culturelles du sous-titrage - Mevel, Pierre-Alexis (Editura Universităţii din Suceava, 2018)
This article offers a comparative analysis of the way Hood films are subtitled into French on the one hand, and banlieue films are subtitled into English on the other. After placing the two genres in their respective cultural environment, this article will examine the way Hood films and banlieue films are subtitled into French and into English respectively. While there are very good reasons why translators may be drawn to the kind of linguistic resources portrayed in Hood films to subtitle banlieue films, and vice versa, we will see that while such translation decisions foster the illusion of symmetry between the two cultures, they also challenge the very notions of source and target language, as well as the application of Venuti’s concepts of domestication and foreignization to the field of subtitling.